Intravesical Blood Clot Retention? How We Manage It, a Tertiary Hospital Preference - Laksita, Tetuka Bagus; Rizaldi, Fikri (Jurnal Kedokteran Brawijaya, 2021)
Intravesical blood clot retention is one of the Urological emergencies. Ongoing haematuria and blood clot formation in the bladder obstruct the urine outflow and lead to urinary retention, abdominal pain, anemia, urinary tract infection (UTI), and renal function deterioration. Most of the cases required cystoscopy blood clot evacuation and definitive surgery to stop the ongoing bleeding. This study aimed to discover the demography, characteristics, management, and complication of patients with intravesical blood clot retention in Dr. Soetomo General Acadenic Hospital, Surabaya from January 2017 until April 2020. This is an observational study, a retrospective-descriptive design. We conducted a review on the medical records of 97 patients, 76 males and 21 females with an average age of 54.9 years old. Of all patients initially treated conservatively using normal saline irrigation with a large three-way catheter (22-24 fr), four were successfully treated without surgery, and 89 patients underwent cystoscopy and definitive surgery. The mean operation time was 69,6 minutes, with an average blood clot volume of 167,7 ml (25-600 ml). Sources of bleeding were mostly originated from malignancy (58%), Benign Prostatic Hyperplasia (BPH) (10%), and hemorrhagic cystitis (7%).Â  The most common comorbidity found was hypertension (13) and chronic kidney disease (10). Based on our experience, managing intravesical blood clot retention with cystoscopy continued with definitive surgery in a one-step procedure is a good approach. Urological malignancy is the most frequent abnormality that causes intravesical blood clot retention.